Activity of the AIB factor observed in prokaryotic and eukaryotic microorganisms - Pospísil, S; Vánová, M; Machurová, V (Folia microbiologica, 1993)
Streptomyces cinnamonensis produces a new substance named AIB (for anti-isobutyrate) factor which, on a solid medium, efficiently counteracts toxic concentrations not only of isobutyrate but also of other salts of short-chain monocarboxylic acids. In the present study we demonstrate that the AIB factor activity is widely spread because this effect was positively detected in 25 of 31 randomly chosen microorganisms (streptomycetes, ascomycetes, zygomycetes and basidiomycetes). The AIB factor produced by the tested microorganisms on an agar media allows for germination, growth, and sporulation of the testing Streptomyces coelicolor on an agar medium containing 20 mmol/L acetate, propionate, butyrate, isobutyrate, valerate, isovalerate, and 2-methylbutyrate. The activity of the AIB factor from different sources towards these substances differs.
Keywords: isobutyráty; biologické faktory; kyseliny pentanové; druhová specificita; Fungi; Substrate Specificity; hemiterpeny; houby; Hemiterpenes; Ascomycota; Butyrates; substrátová specifita; butyráty; Isobutyrates; Pentanoic Acids; Species Specificity; Basidiomycota; Biological Factors; Streptomyces